Upcycling steel slag in producing eco-efficient iron–calcium phosphate cement. (15th October 2022) - Ma, Yue; Luo, Yunlong; Ma, Hongyan; Zhou, Xintao; Luo, Zhongqiu
Abstract: In the present study, steel slag powder (SSP) was utilized as the raw material to prepare iron-calcium phosphate cement (ICPC) by reacting with ammonium dihydrogen phosphate (ADP). The influences of the raw materials (SSP/ADP) mass ratios ranging from 2.0 to 7.0 on the properties and microstructures of ICPC pastes were investigated. The compressive strengths of ICPC pastes at all ages firstly increased and then decreased with the increase of SSP/ADP, and the SSP/ADP of 6.0 gave the highest strength. Crystalline mundrabillaite and amorphous phases [i.e. Fe(OH)3, Al(OH)3 and H4 SiO4 ] were formed as the dominant binding phases through the reactions of the calcium-containing compounds (brownmillerite, monticellite and srebrodolskite) in the steel slag and ADP. Further, ADP could also react with the free FeO contained in the steel slag to yield amorphous iron phosphate phase. BSE analysis indicated that the hydration products formed and growed on the surface of steel slag particles and connect them to form the continuous, dense microstructure of ICPC paste. The utilization of high-volume steel slag as the base component will potentially bring great economic and environmental benefits for the manufacture of phosphate cement. Highlights: A novel iron-calcium phosphate cement (ICPC) is prepared with steel slag as raw material. The effect of weight ratio of raw materials on properties of ICPC paste is elucidated. The hydration products of ICPC paste are dominated by crystalline mundrabillaite and amorphous phases.